Trophic ecology of two co-existing Sub-Antarctic limpets of the genus Nacella: spatio-temporal variation in food availability and diet composition of Nacella magellanica and N. deaurata - Rosenfeld, Sebastian; Marambio Gallardo, Johanna Valeska; Ojeda Villarroel, Jaime Andrés; Pablo Rodriguez, Juan; Gonzalez-Wevar, Claudio; Gerard, Karin Francoise; Contador Mejias, Tamara Andrea; Pizarro, Gemita; Mansilla Muñoz, Andres Omar (My University, 2018)
Interactions between algae and herbivores can be affected by various factors, such as seasonality and habitat structure. Among herbivores inhabiting marine systems, species of the order Patellogastropoda are considered key organisms in many rocky coasts of the world. Nacella species are one of the most dominant macro-herbivores on the rocky shores of the sub-Antarctic ecoregion of Magellan. However, the importance of its key role must be associated with its trophic ecology. The objective of this work was to evaluate spatial and temporal variabilities in the dietary composition of two intertidal Nacella species, considering grazing on macro- (macroalgae) and microscopic (periphyton) food. The composition of periphyton and the availability of macroalgae in the winter and summer seasons were examined at two localities of the Magellanic province, alongside the gut contents of N. magellanica and N. deaurata. The dietary composition differed between the two Nacella species, as well as between seasons and locations. The differences observed in the diet of the two species of Nacella may be mainly due to their respective distributions in the intertidal zone. Both species presented a generalist strategy of grazing, which is relationed to the seasonality of micro- and macroalgae availability and to the variability of the assemblages between the localities. This research was the first to perform a detailed study of the diet of intertidal Nacella species.
Keywords: gastropoda; magellanic province; herbivory; macroalgae; nacellidae; periphyton